Measuring donor loyalty: key reasons why Net Promoter Score (NPS) is not the way. Issue 1 (26th February 2013) - Schulman, Kevin; Sargeant, Adrian
<x xml:space="preserve">Abstract</x> Our paper reviewed the weaknesses of the Net Promoter Score (NPS) as a measure of donor loyalty for fundraisers working in nonprofit organizations, argued that the measure is fundamentally flawed and inappropriate for use in this context, and outlined six major critiques of the NPS approach and offered an alternative way of measuring future loyalty and value. Copyright © 2013 John Wiley & Sons, Ltd.